Upaya Diplomatik Indonesia dalam Penetapan Alur-Alur Laut Kepulauan Indonesia (ALKI) - Agoes, Etty R. (UI Scholars Hub, 2009)
Indonesia is the first Archipelagic State which proposed the establishment of archipelagic sea lane passage as governed in article 53 United Nations Convention Law of the Sea (UNCLOS) 1982. The author opined that basic principle pf Archipelagic State is the unity of land, water, and people. This article explains the archipelagic sea lane passage based on the UNCLOS 1982. Moreover, this article describes the Indonesian efforts on the establishment of archipelagic sea lane passage, includes Indonesian diplomatic effort, within International Maritime Organization.